กระบวนทัศน์พัฒนาเพื่อการพึ่งตนเองของกลุ่มเครือข่ายอินแปงในจังหวัดสกลนคร อุดรธานี กาฬสินธุ์ และมุกดาหาร - ไพใหล สุพัฒน์ (Ph.D. in Social Sciences Journal, 2016)
ดุษฎีนิพนธ์ฉบับนี้มีวัตถุประสงค์เพื่อศึกษา (1) รูปแบบ วิธีการ ความเป็นมาของ กระบวนการเรียนรู้ และการพัฒนากระบวนทัศน์เพื่อการพึ่งตนเองของกลุ่มเครือข่ายอินแปง (2) โครงสร้างระบบเศรษฐกิจ สังคมแบบอินแปงทั้งในแนวลึกและแนวกว้างที่นำไปสู่การพึ่งตนเองของชุมชน (3) ปัจจัยเงื่อนไขของระบบ เศรษฐกิจและสังคมแบบอินแปงต่อแนวทางการพึ่งตนเองและการพัฒนาที่ยั่งยืนผลการวิจัยสรุปได้ดังนี้ 1.) รูปแบบ วิธีการ กระบวนการเรียนรู้และการพัฒนากระบวนทัศน์ของกลุ่มเครือข่ายอินแปงมีรูปแบบ เป็นแบบบอกเล่า แบบกลุ่ม ด้วยการปฏิบัติ การเลียนแบบธรรมชาติ บุคคล ชุมชน และจากวิถีชีวิต โดยใช้ วิธีการเฉพาะของตนเองคือ ประชาวิจัย และพัฒนา การจัดการตนเอง และเครือข่ายทางสังคม การพัฒนา กระบวนทัศน์ของอินแปงแบ่งได้เป็น 3 ยุค 2. )โครงสร้างและระบบ เศรษฐกิจ สังคมแบบอินแปง มีทั้ง ในแนวลึกและแนวกว้างที่นำไปสู่การพึ่งตนเอง ในแนวลึก ประกอบด้วยเศรษฐกิจครัวเรือนหรือแบบพอเพียง และเศรษฐกิจวัฒนธรรม โดยสัมพันธ์กับการประยุกต์ใช้ภูมิปัญญาท้องถิ่นและเทคโนโลยี ในแนวกว้าง ประกอบด้วยเศรษฐกิจชุมชนและวิสาหกิจชุมชน ส่วนระบบสังคมในแนวลึกมีวัฒนธรรมชุมชนเป็นหลัก โดยเฉพาะ ฮีตสิบสอง และแนวกว้างได้แก่ทุนทางสังคมและเครือข่ายทางสังคมที่นำไปสู่การพึ่งตนเองได้ และ 3.) ปัจจัยเงื่อนไขของระบบเศรษฐกิจและสังคมแบบอินแปงที่พึ่งตนเองและแนวทางการพัฒนาที่ ยั่งยืน ประกอบด้วย ปัจจัยภายในและ ปัจจัยภายนอก ส่วนแนวทางการพัฒนาที่ยั่งยืนของอินแปง มีดังนี้ ยกป่าภูพานมาไว้ส่วนส่งเสริมการทำวิสาหกิจชุมชน สร้างสถาบันการเงินและสวัสดิการชุมชน สร้างตลาด สัมพันธ์ (ภายในเครือข่าย) และสร้างสถาบันการเรียนรู้เพื่อปวงชน(มหาวิทยาลัยชีวิต) โดยมีตัวชี้วัดความ สำเร็จการพึ่งตนเองและการพัฒนาที่ยั่งยืน 3 ประการ คือ รอด (Survival) พอเพียง (Sufficiency) และ ยั่งยืน (Sustainability) A SELF –RELIANCE DEVELOPMENT PARADIGM FOR THE INPAENG NETWORKING GROUP IN SAKON NAKHON, UDON THANI, KALASIN, AND MUKDAHAN PROVINCES In this dissertation, the researcher investigates (1) patterns, methods, the historical background of the learning process, and the development of a self-reliance paradigm for the Inpaeng networking group. The researcher also examines (2) the structure of the Inpaeng socio-economic system both in-depth and in wide scope perspectives insofar as community self-reliance is involved. Finally, the researcher studies (3) factorial conditions governing the Inpaeng socio-economic system leading to self-reliance and sustainable development. Findings are as follows 1.)Patterns, and methods of the learning process and the development of the paradigm for the Inpaeng networking group were executed by means of word of mouth and group discussion in which discussed were practices, imitations of nature,individuals, community and ways of life. The specific methods used were involved demographical research and development, self-organization, and social networking. 2.)The structur of the Inpaeng socio-economic system considered from in-depth and in wide scope perspectives showed that the system was becoming self-reliance.In-depth, it consisted of the economy as manifested at household, subsistence, and cultural levels. The economy at these levels was found to be correlated with an application of local wisdom and technology. From a broader perspective, it consisted of community economy and community enterprise. Considered from an in-depth perspective, the social system consisted mainly of community culture, especially the tradition of “Heet Sibsong” or making merits over the course of twelve months. From a broader perspective, it consisted of social capital and social networking leading to self-reliance. 3.) The factors of the Inpaeng socio-economic system involving self-reliance and sustainable development consisted of internal factors and external factors in the Inpaeng networking group in organizing activities. Guidelines for the sustainable development of Inpaeng were as follows: To transform Phuphan Forest into farmland; promoting community enterprise ; establishing financial institutions and community welfare; building market relations(within the network);and constructing a learning institute for the masses(lifelong education) or a learning Institute For Everyone (LIFE University). There are three indicators for success in self-reliance and sustainable development : survival, sufficiency, and sustainability